2014
DOI: 10.3390/ijms150915754
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Induced Human Gastric Cancer BGC-823 Cells Apoptosis by ROS-Mediated ASK1-MKK4-JNK Stress Signaling Pathway

Abstract: The signaling mediated by stress-activated MAP kinases (MAPK), c-Jun N-terminal kinase (JNK) has well-established importance in cancer. In the present report, we investigated the effects of curcumin on the signaling pathway in human gastric cancer BGC-823 cells. Curcumin induced reactive oxygen species (ROS) production and BGC-823 cells apoptosis. Inhibition of ROS generation by antioxidant (NAC or Trion) significantly prevented curcumin-mediated apoptosis. Notably, we observed that curcumin activated ASK1, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 44 publications
5
44
0
1
Order By: Relevance
“…Moreover, curcumin was demonstrated to induce marked apoptosis in human gastric cancer cells in a dose-dependent manner, which was conveyed by the increase in TUNeL-positive cells and the apoptosis population by flow cytometry, as well as the upregulation of apoptosis-related proteins. Consistent with our findings, studies have majorly focused on apoptosis to elucidate the mechanisms by which curcumin exerts its anticancer effect (16,28). However, the role of curcumin-induced autophagy and the exact mechanism involved in the interaction between apoptosis and autophagy with curcumin treatment have not been generally clarified, particularly in human gastric cancer.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, curcumin was demonstrated to induce marked apoptosis in human gastric cancer cells in a dose-dependent manner, which was conveyed by the increase in TUNeL-positive cells and the apoptosis population by flow cytometry, as well as the upregulation of apoptosis-related proteins. Consistent with our findings, studies have majorly focused on apoptosis to elucidate the mechanisms by which curcumin exerts its anticancer effect (16,28). However, the role of curcumin-induced autophagy and the exact mechanism involved in the interaction between apoptosis and autophagy with curcumin treatment have not been generally clarified, particularly in human gastric cancer.…”
Section: Discussionsupporting
confidence: 87%
“…However, the effect of curcumin on human gastric cancer and the underlying mechanisms have not been well documented. Previous studies demonstrated that curcumin attenuates gastric cancer cell proliferation, induces apoptotic cell death and suppresses lymphatic vessel density in vivo or in vitro (27)(28)(29). In the present study, we provided the first evidence that curcumin inhibited cell growth and induced protective autophagy against apoptotic cell death in human gastric cancer.…”
Section: Discussionsupporting
confidence: 64%
“…The present study showed that cambogin treatment induced ROSdependent activation of ASK-1, SEK1/MKK4, MKK7, and JNK/ SAPK. The duration of JNK/SAPK activation regulates specific proapoptotic/antiapoptotic targets like Bcl-2 family of proteins, which is implicated in the apoptotic response when cells are exposed to several chemotherapeutic agents (33,37,38). Indeed, the blockage of JNK/SAPK activation attenuated the anticancer activity of cambogin, further supporting a central role of JNK/ SAPK in mediating the proapoptotic effect of cambogin.…”
Section: Discussionmentioning
confidence: 90%
“…Although most of these studies were conducted as in vitro studies, clinical trial studies were not completely reviewed. Many studies investigated the antiinflammatory and antioxidant effects of curcumin in a variety of conditions (18) . For example, it was reported that curcumin may be useful for treating gastric injuries by gastric peroxide inhibition, ROS, leukocyte infiltration inhibition, and reduction of the cell adhesion molecule level (ICAM-1) and tumor necrosis factor alpha (TNF-a) (23) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the changes and damages of oxidative deoxyribonucleic acid (DNA) associated with H. pylori gastritis as well as stomach cancer are due to the imbalance between endogenous antioxidants, such as superoxide dismutase (SOD), Glutathione peroxidase (GPx), catalase (CAT), and ascorbic acid and lipid peroxidation product accumulation in the cells (7,26) . Given the importance of oxidative stress in gastritis associated with H. pylori, one of the todays' aspects of treatment in this context, is the use of natural antioxiCurcumin in combination with triple therapy regimes ameliorates oxidative stress and histopathologic changes in chronic gastritisassociated Helicobacter pylori infection dants in these patients (17,18) . Curcumin is a hydrophobic polyphenol isolated from Curcuma longa L (rhizomes of the Zingiberaceae family) (5) .…”
Section: Introductionmentioning
confidence: 99%